Indirect measurement of stress distribution in quartz particles embedded in a glass matrix by using confocal Raman microscopy. Issue 10 (December 2015) - Reinosa, J.J.; del Campo, A.; Fernández, J.F.
Abstract: Differences in thermal expansion during the sintering process promote the appearance of stresses in a glassy matrix having crystalline particles. The stress distribution is critical in the performance of materials as porcelains that are widely used and produced in large volume by the industry. A controversy still exists on how crystalline phases as quartz strengthen the glass matrix. In this work, the existence of stress into quartz grains and into glassy phase in porcelain is evidenced by using Confocal Raman Microscopy. Surface and depth profile images of Raman shift show an anisotropic stress distribution in crystalline particles. Quartz grains are under tensile stress into the glassy phase and the stress is accommodated through the rotation of the rigid tetrahedrons around the (001) axes and the decreasing of the bonding constant forces for the Si–O bonds. The appearance of cracks into the crystalline particles is due to the stress asymmetry exceeding the tensile limit. The proposed mechanism is relevant for the design of new glassy-matrix based composites.